2019
DOI: 10.1097/jan.0000000000000272
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Lifestyle and Family Functioning Among Family Members of Amphetamine Abusers in Southeast Iran

Abstract: Introduction: Drug abuse is a social event and one of the worse health problems in the current age. Nowadays, the inclination of young people has changed from traditional drugs to more sophisticated and industrial drugs such as ecstasy, glass, and crack. Increasing drug abuse can be sought in families' lifestyles as an effective factor on individuals' health. The disturbance in family functioning can be associated with an individual's antisocial behaviors like addiction. Therefore, the current study is aimed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…14 METH abuse has prominent CNS side effects such as psychosis and depression. 28,29 Alavijeh et al (2019) showed that METH consumption induced anxiety-like behaviors via modulation of oxytocin receptors in methamphetamine addicted rats the same as our finding. 30 These behavioral changes can also be due to the high and quick distribution of METH in the body and enhancement of synaptic and extra-synaptic levels of serotonin, noradrenaline and dopamine.…”
Section: Discussionsupporting
confidence: 88%
“…14 METH abuse has prominent CNS side effects such as psychosis and depression. 28,29 Alavijeh et al (2019) showed that METH consumption induced anxiety-like behaviors via modulation of oxytocin receptors in methamphetamine addicted rats the same as our finding. 30 These behavioral changes can also be due to the high and quick distribution of METH in the body and enhancement of synaptic and extra-synaptic levels of serotonin, noradrenaline and dopamine.…”
Section: Discussionsupporting
confidence: 88%
“…Another study conducted among spouse caregivers of patients with dementia showed that deterioration of relationship quality perceived by caregiver was specifically associated with the presence of behavioral problems, notably apathy of patients [28]. Other factors associated with family relationship quality included factors of family structure (e.g., family type, family size, and residential status), lifestyle, and genetic and environmental factors [6,29,30].…”
Section: Introductionmentioning
confidence: 99%